Publicity and pathos: Andy Warhol's Marilyn Diptych (1962) in context. Issue 2 (1st December 2015) - Needham, Gary
Andy Warhol's Marilyns are often interpreted as a celebration of her stardom rather than a commentary on it. In Marilyn Diptych, made shortly after her death, Warhol searches beneath the facade at the private trauma of Norma Jean; Marilyn's luminosity seemingly consumed in the darkness of the black acrylic paint.